Poetics work «Muginul-Murid» (XIV с.) (Journal of Oriental Studies, 2016)
The article discusses the poetic of work “Muinul-murid” written during the Golden Horde. In addition the provides conclusions about the author of this work.
Keywords: turkology; text; literature; manuscript; literature Monuments; rhythm; author.